Slavery, empathy, and pornography - Wood, Marcus (OUP E-Books., 2002)
Slavery, Empathy, and Pornography considers the operations of slavery and of abolition propaganda on the thought and literature of English from the late-eighteenth to the mid-nineteenth centuries. Incorporating materials ranging from canonical literatures to the lowest form of street publication, Marcus Wood writes from the conviction that slavery was, and still is, a dilemma for everyone in England, and seeks to explain why English society has constructed Atlantic slavery in the way it has. He takes on the works of canonic eighteenth- and nineteenth-century white authors which claimed, when written, to 'account' for slavery, and asks with some scepticism what kind of 'truth' they hold.; Taking an interdisciplinary approach, chapters focus on the writings of the major Romantic poets, English Radicals William Cobbett and John Thelwall, the Surinam writings of John Stedman, the full range of slavery texts generated by Harriet Martineau, John Newton, and the social prophets Carlyle and Ruskin. Slavery, Empathy, and Pornography also contains a radical new critique of the operations of slavery within the work of Austen and Charlotte Bronte.